Multi‐functional commercial solar photovoltaic plant integrated to three‐phase low voltage AC network. Issue 12 (20th April 2021) - Modi, Gaurav; Singh, Bhim
Abstract: This study presents the commercial solar PV plant (SPVP) operation, integrated into the low voltage (LV) AC network. The SPVP has the multi‐functional operational capability. It feeds the PV array generated power to loads and the AC network, while ensuring the power quality improvement at the point of common coupling (PCC) as per the IEEE std. 519, irrespective of the load characteristic (linear/nonlinear and balanced/unbalanced). The SPVP minimises the line losses in the AC network by recouping the load reactive power requirement locally. Moreover, the SPVP operates in either maximum power extraction (MPE) mode or constant power generation (CPG) mode, depending upon the rise in PCC voltage amplitude during the peak PV array power generation and low load demand condition. The SPVP switches between the MPE and the CPG modes during the high rise in PCC voltage amplitude and regulates the PV array generated power to protect itself and the load connected at PCC. In this study, an adaptive filter technique based on maximum correntropy criterion is used for the PQI, and the perturb and observe based algorithm is used for MPE. A simulation model and reduced rating hardware prototype are developed to validate the system's performance.